Performance analysis of a wind tower in combination with an underground channel - Sadeghi, Hosein; Kalantar, Vali (Sustainable cities and society, 2018)
•Performance of a novel design of a wind towers in combination with an underground channel was investigated.•The research was performed numerically and the computational model was generated and validated based on previous close experimental works.•For two types of wet and dry channels, 7.6 and 15.4° temperature drop was achieved for the entering air to the room, respectively.•Using wet channel, the air relative humidity was increased by 52% with the rate of water consumption of 0.006kg/s.•Considering heat comfort conditions, wet channel is more effective in comparison with the dry one for cooling application of this new system. In the present work, a new method was introduced in order to improve the performance of wind towers. In hot seasons, underground temperature is lower than that of the surface and it can be used as a free cooling source. Accordingly, in this work, the use of a wind tower in combination with an underground channel for passing the air was introduced and investigated. This research was done for two cases of dry and wet channels. In order to solve this problem numerically, governing equations were discretized using finite volume method, SIMPLE algorithm was used for pressure-velocity coupling and k−ε model was chosen as turbulent model. Considering the weather conditions of Yazd in Iran as a sample of the regions where using wind towers is common, this study concluded that using dry or/and wet channels, the entrance air temperature was reduced from 42°C to 34.4°C and 26.6°C, respectively. Using the wet channel, the relative humidity of air increased by 52%, from the initial value of 14% to 66%, and the water consumption of 0.006kg/s and air mass flow rate of 0.8466kg/s were achieved. Results showed that this method is efficient due to thermal comfort conditions.